2015
DOI: 10.9789/2175-5361.2015.v7i4.3467-3478
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of nursing language to the practice with elderly residents in a long term psychiatric institution: cross mapping

Abstract: Objective: to map the free terms of nursing records and compare with the Nursing Diagnosis classification. Method: quantitative, documentary and retrospective approach, cross mapping type. There were 30 medical records analyzed of elderly women with psychiatric disorders living in two long-term institutions. The data collection took place in from August 2013 to March 2013 in two stages. Results: diagnostics more occurring were: ineffective health self-control; Impaired swallowing; Self-care deficit for intimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…It is also worth noting that the level of evidence used to classify the selected studies was from the Joana Briggs Institute. 12 The analysis and synthesis of the articles were carried out in a descriptive way to expose, in detail, the literature on Nursing Diagnoses according to NANDA-I and provide, in the future, subsidies for the clinical practice of nurses in Psychosocial Rehabilitation. It is revealed that, of the four articles included in this integrative review, one was published in English and three articles in Portuguese; the articles were presented between 2003 and 2015, and, in relation to the level of evidence, articles were classified as observational, descriptive and cross-sectional.…”
mentioning
confidence: 99%
“…It is also worth noting that the level of evidence used to classify the selected studies was from the Joana Briggs Institute. 12 The analysis and synthesis of the articles were carried out in a descriptive way to expose, in detail, the literature on Nursing Diagnoses according to NANDA-I and provide, in the future, subsidies for the clinical practice of nurses in Psychosocial Rehabilitation. It is revealed that, of the four articles included in this integrative review, one was published in English and three articles in Portuguese; the articles were presented between 2003 and 2015, and, in relation to the level of evidence, articles were classified as observational, descriptive and cross-sectional.…”
mentioning
confidence: 99%
“…12 Estudo realizado no Rio de Janeiro confirma essa prevalência. 34 Diante do exposto, enfatiza-se a importância de incentivar e fortalecer os vínculos e a reinserção do idoso no ambiente familiar, responsabilizando a família pelos seus cuidados. Compreende-se também, que a equipe multiprofissional da instituição de longa permanência possui a função de auxiliar os idosos no processo de institucionalização e ofertar assistência social, emocional, física e mental.…”
Section: Discussionunclassified
“…Usually, an ineffective health response for a short period of time, considered reversible, reflecting in the memory and/ or in other cognitive abilities, is acute confusion (15) . However, if there are permanent difficulties (after treatment of reversible causes), the diagnosis is IM (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) . Finally, if the problems reach other cognitive areas, added to demonstration of dependency, the diagnosis is CC (30,(33)(34) .…”
Section: Discussionmentioning
confidence: 99%
“…The ND of IM was prevalent in 61,61% of hospitalized elders on a specialized unit of a general Brazilian hospital (9) . In addition, a prospective study of 123 older adults living in a long-term care institution found IM in 31% of participants (10) , while the ND CC was identified in 90% of older adults living in a long-term care institution (11) .…”
Section: Introductionmentioning
confidence: 99%